Analisis Hubungan Faktor Perilaku Pengendalian Pasien Diabetes Mellitus dengan Kadar Gula Darah di Puskesmas Sukorame Kediri: Analysis of the Relationship Between Diabetes Mellitus Patients's Control Behavior Factors With Blood Sugar Levels at Sukorame Public Health Center, Kediri - Laili, Nur Fahma; Probosiwi , Neni; Dianati , Syarofina; vitria, Laili; hidayah, lailatul (Universitas Kadiri, 2025)
Diabetes mellitus is characterized by increased blood sugar levels above normal limits (hyperglycemia). Factors that can support a person's risk of developing diabetes mellitus include an unhealthy lifestyle, such as obesity, high body mass index (BMI), lack of physical activity, consumption of foods high in carbohydrates, protein, fat and fiber, and smoking habits. Therefore, the aim of this study was to find out about the relationship between behavioral factors in controlling diabetes mellitus patients and blood sugar levels in diabetes patients at health service facilities. The number of samples was 93 respondents using the Physical Activity Questionnaire (GPAQ) questionnaire, Carbohydrate Consumption Frequency Questionnaire (FFQ), Fiber Consumption Frequency Questionnaire (FFQ), Compliance Questionnaire (MARS) and random blood sugar level results (GDS). The data results show that there is a relationship between behavioral factors for controlling type 2 diabetes mellitus such as physical activity (0.034<0.05), frequency of carbohydrate consumption (0.039<0.05), frequency of fiber consumption (0.028<0.05), medication compliance (0.016<0.05) with blood sugar levels.